2021
DOI: 10.3390/microorganisms9020388
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Chromosomal crpP-like Genes Is Not Always Associated with Ciprofloxacin Resistance in Pseudomonas aeruginosa Clinical Isolates Recovered in ICU Patients from Portugal and Spain

Abstract: CrpP enzymes have been recently described as a novel ciprofloxacin-resistance mechanism. We investigated by whole genome sequencing the presence of crpP-genes and other mechanisms involved in quinolone resistance in MDR/XDR-Pseudomonas aeruginosa isolates (n = 55) with both ceftolozane-tazobactam susceptible or resistant profiles recovered from intensive care unit patients during the STEP (Portugal) and SUPERIOR (Spain) surveillance studies. Ciprofloxacin resistance was associated with mutations in the gyrA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 33 publications
1
17
1
Order By: Relevance
“…The acquisition of the crpP gene, coding for a ciprofloxacin-modifying enzyme [ 63 ] was detected in our strains, all of them bearing the non-synonymous mutations K4R and G7D in CrpP, when compared with the CrpP (GenBank accession: NG_062203). A very recent study conducted on a large number of P. aeruginosa isolates from Portugal and Spain showed that CrpP proteins with the amino acid substitutions K4R and G7D were the most predominant variants among the population analyzed [ 64 ]. A reduced activity of CrpP on ciprofloxacin was previously observed when missense mutations occurred in the amino acid position G7, indicating that this is an essential residue for the enzymatic activity of CrpP [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…The acquisition of the crpP gene, coding for a ciprofloxacin-modifying enzyme [ 63 ] was detected in our strains, all of them bearing the non-synonymous mutations K4R and G7D in CrpP, when compared with the CrpP (GenBank accession: NG_062203). A very recent study conducted on a large number of P. aeruginosa isolates from Portugal and Spain showed that CrpP proteins with the amino acid substitutions K4R and G7D were the most predominant variants among the population analyzed [ 64 ]. A reduced activity of CrpP on ciprofloxacin was previously observed when missense mutations occurred in the amino acid position G7, indicating that this is an essential residue for the enzymatic activity of CrpP [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, quinolones’ resistance is either chromosomally or plasmid-mediated through different mechanisms. 11 , 12 These mechanisms act separately or in combination leading to various degrees of quinolone resistance that range from reduced susceptibility to complete resistance. 13 …”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, due to the irrational use of quinolones, resistance to this group has been increasing over the last years with the emergence of multi-drug resistant (MDR) P. aeruginosa . 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations